Personal Constructs of Mind-Body Identity in People Who Experience Medically Unexplained Symptoms. Issue 4 (2nd October 2019) - Sanders, Tom; Winter, David; Payne, Helen
Abstract : "Medically unexplained symptoms" (MUS) refers to chronic physical symptoms without a clear medical cause, which produce significant levels of distress and functional impairment. This project modified the repertory grid technique to explore how twenty participants experiencing MUS construed self and others in bodily and psychological ways. Findings suggested that symptoms are well integrated within participants' wider mind–body construct systems. Increased distance between how self in general is construed compared to self when symptoms are worst was associated with reduced anxiety. Measuring intrapersonal and interpersonal implicative dilemmas suggested that moral and relational construing of identity is affected by MUS.